2017
DOI: 10.1016/j.smim.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy for food allergy

Abstract: Food allergy is a pathological, potentially deadly cascade of immune responses to molecules or molecular fragments that are normally innocuous when encountered in foods, such as milk, egg, or peanut. As the incidence and prevalence of food allergy rise, the standard of care is poised to advance beyond food allergen avoidance coupled with injectable epinephrine treatment of allergen-induced systemic reactions. Recent studies provide evidence that oral immunotherapy may effectively redirect the atopic immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 94 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…Indeed, IgG has been shown to inhibit IgE‐mediated mast cell and basophil activation through two mechanisms: antigen interception (competition with IgE epitopes), and cross‐linking of FcεRI with the inhibitory receptor FcγRIIB [107]. Oral immunotherapy (OIT), which is used to desensitize food allergic subjects, increases levels of food‐specific IgG [108, 109]. It has thus been suggested that such IgG (and especially IgG4 that has low affinity for activating FcγRs [110]) can participate in the protective effects conferred by OIT [108, 109].…”
Section: Role Of Ige In Food Allergy and Anaphylaxis: Lessons From Momentioning
confidence: 99%
“…Indeed, IgG has been shown to inhibit IgE‐mediated mast cell and basophil activation through two mechanisms: antigen interception (competition with IgE epitopes), and cross‐linking of FcεRI with the inhibitory receptor FcγRIIB [107]. Oral immunotherapy (OIT), which is used to desensitize food allergic subjects, increases levels of food‐specific IgG [108, 109]. It has thus been suggested that such IgG (and especially IgG4 that has low affinity for activating FcγRs [110]) can participate in the protective effects conferred by OIT [108, 109].…”
Section: Role Of Ige In Food Allergy and Anaphylaxis: Lessons From Momentioning
confidence: 99%
“…Several approaches have been developed recently to reduce the occurrence of adverse reactions during milk OIT. Combining OIT and treatment with the monoclonal anti-IgE antibody omalizumab allowed an acceleration of the build-up phase and the reduction of the frequency and severity of side-effects in cow’s milk allergic children, but varying outcomes of efficacy were observed [121,122,123,124,125,126]. However, the high costs of this treatment have to be considered.…”
Section: Current Treatment Strategies For Cow’s Milk Allergymentioning
confidence: 99%
“…Several immunological changes that occur in the course of OIT have been described, as a decrease of allergen-specific IgE and the induction of allergen-specific IgG4 antibodies, a decline in antigen-specific Th2 cells, and the induction of regulatory T cells [126].…”
Section: Current Treatment Strategies For Cow’s Milk Allergymentioning
confidence: 99%
“…Oral immunotherapy (OIT) to treat cow's milk, peanut, and hen's egg allergies has been shown to reduce clinical symptoms upon food challenge but unsuccessfully maintained the protective state upon discontinuation of the therapy [8]. Effective desensitization of effector cells like mast cells and basophils in combination with active modulation of the adaptive immune response via antigen-presenting cells and T and B lymphocytes is key mechanisms in OIT [9]. The use of dietary adjuvants with immunomodulatory properties might open a new window of opportunities to improve the efficacy of OIT for food allergies.…”
Section: Introductionmentioning
confidence: 99%